A study about the adoption of the practice of cleaner production in industrial enterprises certified ISO 14001 in Brazil - de Oliveira, José Augusto [UNESP]; de Oliveira, Otávio José [UNESP]; de Oliveira Santos, Sílvia Renata [UNESP] (My University, 2012)
The growth of developing countries has significantly driven the industrial activity, which has generated employment and development. However, this scenario also has its downside, in other words, due to lax laws and consumers still little conscious of the importance of effective environmental protection. The industry has been the main degrading environment in these nations. However, some technical programs and management tools have been used to minimize this serious problem, especially if the environmental management system ISO 14001:2004 and Cleaner Production (CP). For these reasons, this book chapter has as main objective to present good practices of cleaner production adopted by four industrial companies operating in Brazil with high profile and certified according to ISO 14001:2004. The companies act in the area of cellulose and paper and chemical. Their management systems ISO 14001:2004 will be characterized and the major practices of Cleaner Production will be reported. In general terms, it was observed that the EMS has greater coverage of these companies that ISO 14001:2004 due to demands from the processes related to cleaner production. They use specific methodologies and specific classifications to the elements of CP and do not follow exactly the elements proposed by UNIDO (United Nations Industrial Development Organization). It was observed that the companies have achieved significant results by adopting the cleaner production achieved environmental and financial gains from the reuse of production inputs, internal recycling in the production process, cost reduction with treatment and disposal of waste, reducing spending with environmental liabilities promoted by prevention of the pollution, among others, which are the main benefits expected by the practice of CP. © 2012 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Brazil; Cleaner production; Environmental management; Industrial companies; ISO 14001:2004